From five to one: Sandyella species (Palaemonidae) are distinct ontogenetic stages of a single species. (9th June 2020) - Ávila‐García, Ariadna; Sánchez, Carlos; Borda, Elizabeth; González‐Acosta, Bárbara; Huato‐Soberanis, Leonardo; Gómez‐Gutiérrez, Jaime
Abstract: The palaemonid genus Sandyella includes S. tricornuta (Isla María Madre, Mexico), S. mclaughlinae, S. bicornuta, S. quadricornuta and S. sexicornuta (Clipperton Island, France). These species were first described in the genus Chacella based on collections of few individuals and limited to no ecological information. Sandyella was later erected to differentiate Chacella kerstitchi from Chacella tricornuta and Chacella mclaughlinae . The remaining three Chacella species (<3 mm cephalothorax length) were later also moved to Sandyella and distinguished mainly based on variation in the less than three protuberances on the cephalothorax and number of protuberances on the abdomen. Since their description from their type localities, only Sandyella tricornuta has been additionally recorded from Bahía de La Paz, Mexico. Collections done at 13 locations along the Gulf of California (2009–2010) yielded 2, 905 specimens including representatives of all Sandyella species as epibionts of 57 black coral colonies Antipathes galapagensis, which prompted a closer taxonomic examination. Based on observations of live and preserved specimens, including type material, population cephalothorax size frequency and mitochondrial COI data, we inferred that all current Sandyella species (a) exhibit three protuberances on the cephalothorax; (b) cephalothorax length and number of protuberances appear to be progressive among species; (c) species exhibit high COI sequence similarity; and d) the five Sandyella species were observed cohabiting the same black coral colony. Therefore, we conclude that the five current Sandyella species are in fact distinct ontogenetic stages of a single species, S. tricornuta, and our results of a morphological Bayesian analysis led us conclude that this species belongs to the genus Sandyella rather than Chacella.